Integrating: A managerial practice that enables implementation in fragmented health care environments. Issue 3 (July 2017) - Kerrissey, Michaela; Satterstrom, Patricia; Leydon, Nicholas; Schiff, Gordon; Singer, Sara
Abstract : Background: How some organizations improve while others remain stagnant is a key question in health care research. Studies identifying how organizations can implement improvement despite barriers are needed, particularly in primary care. Purposes: This inductive qualitative study examines primary care clinics implementing improvement efforts in order to identify mechanisms that enable implementation despite common barriers, such as lack of time and fragmentation across stakeholder groups. Methodology: Using an embedded multiple case study design, we leverage a longitudinal data set of field notes, meeting minutes, and interviews from 16 primary care clinics implementing improvement over 15 months. We segment clinics into those that implemented more versus those that implemented less, comparing similarities and differences. We identify interpersonal mechanisms promoting implementation, develop a conceptual model of our key findings, and test the relationship with performance using patient surveys conducted pre-/post-implementation. Findings: Nine clinics implemented more successfully over the study period, whereas seven implemented less. Successfully implementing clinics exhibited the managerial practice of integrating, which we define as achieving unity of effort among stakeholder groups in the pursuit of a shared and mutually developed goal. We theorize that integrating is critical in improvement implementation because of the fragmentation observed in health care settings, and we extend theory about clinic managers' role in implementation. We identify four integrating mechanisms that clinic managers enacted: engaging groups, bridging communication, sensemaking, and negotiating . The mean patient survey results for integrating clinics improved by 0.07 units over time, whereas the other clinics' survey scores declined by 0.08 units on a scale of 5 ( p = .02). Practice Implications: Our research explores an understudied element of how clinics can implement improvement despite barriers: integrating stakeholders within and outside the clinic into the process. It provides clinic managers with an actionable path for implementing improvement.